IMPLEMENTATION OF EXCLUSIVE LEARNING MODEL IN TEACHING ENGLISH - Marpaung, Devi Annisa; Damayanti, Yusnika; Yusnaini, Yusnaini; Nurhasanah, Nurhasanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
The purpose of this research is to find out how the Exclusive learning model is implemented in the English teaching and learning process and find out how students respond to the Exclusive learning model. This research is a qualitative descriptive research that focuses on the process of implementing the Exclusive learning model in English Language Teaching. This is related to instructions from the Exclusive learning model to create interesting activities in the classroom during the English learning process. This research method was applied to undergraduate students of Public Health at Nurul Hasanah University, Kutacane. Researchers found that the exclusive learning model can make students improve their skills in English; Speaking, Reading, Writing and Listening. Researchers suggest to English teachers to use the Exclusive learning model as a learning method used in teaching English because the Exclusive learning model can make students develop their creative ideas.